PENGARUH PEMBELAJARAN INKUIRI TERBIMBING (GUIDED INQUIRY) TERHADAP MOTIVASI DAN HASIL BELAJAR SISWA - Daniswara, Agustinus Gigih; Ningsih, Kurnia; Ariyati, Eka (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis research seeks to identity the effect of guided inquiry learning model toward students? motivation and their achievement on a lesson about virus at Grade X of SMA 2 Sungai Ambawang. The research used quasi experimental design with a non-equivalent control group design. Data for this research were collected through intact group. Class XC was categorised as a experimental group and Class XA was referred to the control group. The research instruments were motivational questionnaires and tests. The result showed that the average percentage of motivation between experimental and control groups were 82.78% and 78.22%. The results of the Mann-Whitney U test, obtained by Zcount (-1.98) < -Ztable (-1.96) means that there are significant differences between the learning outcomes of students taught using Guided Inquiry and conventional learning models. Further, the mean value for test result were 14.67 and 13.37. The effect size was 0.46 which can be classified medium and had an effect by 17.72%. Keyword: Guided inquiry, learning motivation, virus test result